Preliminary Screening of Antibacterial Activity Using Crude Extracts of Hibiscus rosa sinensis - Sangeetha Arullappan,; Zubaidah Zakaria,; Dayang Fredalina Basri , (Tropical Life Sciences Research, 2009)
Hibiscus rosa sinensis, a member of the Malvaceae family, is widely cultivated in the tropics as an ornamental plant. It is often planted as a fence or hedge plant, and has several forms of flowers with varying colours. It is also used in traditional medicine to induce abortion, ease menstrual cramps, assist in childbirth and relieve headache, fever and inflammation. In this study, we evaluated the antibacterial activity of H. rosa sinesis extract using a disc diffusion method. Crude petroleum ether extract, ethyl acetate extract and methanol extract from the leaves, stems and flowers of the plant were prepared using a cold extraction technique. These extracts were tested at concentrations ranging from 4 mg/disc to 0.017 mg/disc against methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumonia. The petroleum ether extract from the leaves, stems and flowers and methanol extract from the leaves showed inhibition zones with diameters > 12 mm against MRSA. Overall, the petroleum ether extract from flowers at concentrations of 4 mg/disc and 2 mg/disc displayed the strongest inhibition zones of 18.6 ± 2.85 mm and 18.5 ± 0.29 mm, respectively, as compared to vancomycin (30 µg/ml), which did not differ significantly from the 18.0 ± 0.10 mm size of the vancomycin (30 µg/ml) inhibition zone (p < 0.05). In conclusion, H. rosa sinensis extract is a potential antibacterial agent for treating MRSA infection. Hibiscus rosa sinensis berasal daripada famili Malvaceae dan ditanam sebagai tumbuhan hiasan dengan luasnya di negara tropika, serta mempunyai pelbagai warna. Kegunaan tradisional bunga ini adalah untuk merawat sakit kepala, demam, kekejangan semasa haid, memudahkan dalam kelahiran anak, penawar bagi racun, ubat sakit mata serta merawat inflamasi. Kajian ini telah dilakukan untuk menilai aktiviti antibakteria melalui kaedah resapan agar. Ekstrak kasar petroleum eter, ekstrak kasar etil asetat dan ekstrak kasar metanol daripada daun, batang dan bunga telah diperolehi melalui kaedah rendaman sejuk. Kesemua ekstrak kasar pada kepekatan 4 mg/cakera hingga 0.017 mg/cakera telah diuji ke atas bakteria methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus aureus, Eschericia coli, Pseudomonas aeruginosa dan Klebsiella pneumonia. Ekstrak petroleum eter daripada batang, daun dan bunga serta ekstrak metanol daripada daun menunjukkan diameter zon perencatan > 12 mm terhadap MRSA. Secara keseluruhan, ekstrak petroleum eter daripada bunga pada kepekatan 4 mg/cakera dan 2 mg/cakera mempamerkan zon perencatan yang tertinggi iaitu 18.6 ± 2.85 mm dan 18.5 ± 0.29 mm masing-masing berbanding dengan vancomycin (30 µg/ml) yang tidak berbeza secara signifikan dari saiz zon perencatan vancomycin (30 µg/ml) (p < 0.05). Kesimpulannya, ekstrak H. rosa sinensis berpotensi sebagai agen antibakteria terhadap infeksi MRSA.